“It’s easier to understand”: the effect of a speaker’s accent, visual cues, and background knowledge on listening comprehension - Barros, Patricia Cristina Monteiro de (Kansas State University, 2010)
The increasing number of non-native English-speaking instructors in American universities constitutes an issue of controversial debate, concerning the interaction of native English- speaking students and non-native English speaking instructors. This study investigated the effects of native or non-native speakers and audiovisual or audio-only lecture mode on English native speakers’ comprehension and memory for information from a classroom lecture, measuring both factual memory and strength of pragmatic inferences drawn from the text. College students (N = 130) were tested on their comprehension of information derived from basic entomology lectures given by both an English native speaker and an English non-native speaker GTA. Participants also evaluated both lecturers in terms of communication skills. Results indicated that participants evaluated the native speaker as having better communication skills, which is in accordance with previous studies suggesting that both the difficulty of understanding non-native-accented speech (Reddington, 2008) and the possibility of prejudice triggered when listeners hear a non-native accent (Bresnahan et al., 2002) influence listeners’ evaluations of English non-native speaker instructors. Results revealed that familiarity with the topic also played an important role in listening comprehension, especially for lectures given by the non-native speaker. Likewise, the access to visual cues (gestures and facial expressions) enhanced understanding, but it was not a pre-requisite for adequate comprehension when the topic of the lectures did not require visual information. These findings were consistent with the polystemic speech perception approach (Hawkins, 2003), in that it is not essential to recognize all words in text in order to make connections with previous knowledge and construct meaning. Furthermore, overall participants took longer to answer questions from lectures given by the non-native speaker than by the native speaker. This suggests that non-native-accented speech may require more time to answer questions related to that speech, although listeners can adapt to it quickly (Derwing, 1995). Findings from this study are important in suggesting tools for thinking about how different aspects of a lecture can contribute to the learning process. Implications for further research are addressed.
Keywords: Listening comprehension; English native speaker graduate teaching assistant; English non-native speaker graduate teaching assistant; Instructor's communication skills; Instructor's accent; Visual cues; Psychology, Cognitive (0633)